PENDAMPINGAN KEGIATAN MENYIKAT GIGI SELAMA 7, 21, 35 HARI OLEH ORANG TUA PADA ANAK POS PAUD PANDEGA SIWI KELURAHAN TLOGOSARI KECAMATAN PEDURUNGAN KOTA SEMARANG - Ani Subekti; Endra Nastiti Donasari; Bambang Sutomo; Sulur Joyo Sukendro (Jurnal Kesehatan Gigi, 2017)
TITLETHE PARENTS-DESIGNED PROGRAM TO SUPPORT TOOTH BRUSHING DURING 7, 21, 35 DAYS OF YOUNG CHILDREN IN PAUD PANDEGA SIWI, TLOGOSARI, PEDURUNGAN, SEMARANG CITYABSTRACTDental and oral health services are provided by looking at the needs of the target. For pre-school age (playgroup, kindergarten A, and kindergarten B) service more priority prevention and familiarize healthy life behavior. The maintenance of dental hygiene and gum especially brushing morning and night before going to bed as prevention of dental and oral disease is considered important at this age is to get good dental health quality in the future. The purpose of study is a change in the behavior of students PAUD Pandega Siwi in terms of ability to brush your teeth properly and correctly.Implementation of study is done in July - August 2017 with the target devotion is Childhood PAUD counted 41 and her parents. The pretest is the examination of tooth brushing behavior and the level of dental hygiene of children of early childhood. Intervention stage in the form of counseling on how to brush their teeth with the help of multimedia tools and demonstration using phantom on the students of PAUD and parents. Monitoring I (7th day), II (21st day) and 3rd (35th day) are Teacher's guidance to parents in the implementation of home toothbrushes at PAUD students. Posttest evaluation is done the same as in the initial examination.The results of the activity is a change in the level of dental hygiene of children PAUD Pandega Siwi and brushing behavior teeth. Brushing behavior changes in terms of previous toothbrushing technique back and forth to turn around. The conclusion is the parent's assistance in the home is very instrumental in improving the level of dental hygiene and brushing behavior. Key words : Toothbrushing assintance, PAUD Pandega Siwi